GPS navigation system - Shuhairie, Mohammad (2008)
A general automotive navigation system is a satellite navigation system designed for use in automobiles. It typically uses GPS to acquire position data to locate the user on a road in the unit's map database. In the other side an automated guided vehicle or so called automatic guided vehicle (AGV) is a system designed to perform an unmanned travel of a vehicle. This vehicle can be used in many area especially dangerous places such as at harbor, surveying and military purpose. There are two main sensors AGV use for navigation, a wired sensor and a wireless sensor. The purpose of this project is to combine the concept of both systems to produce a prototype of an AGV navigated by a combination of GPS receiver and digital compass instead of using camera, guide tape, laser, inertial or gyroscopic. The project called as GPS Navigation System. The whole project can be divided into two main parts. The first part is concern on the hardware development where all electronics component are connected via the circuit design using wire wrapping technique. A GPS receiver, digital compass, RF receiver, and keypad are the input components while RF transmitter, LED, and LCD display are the output components. All of this input and output devices are connected to a PIC14F8550 microcontroller. The second part is about software programming which used to control the whole operation of the system. The program is written using MikroBasic and downloaded to the PIC18F4550 using PIC programmer after compiled into a *.hex file. As a conclusion, this system is designed to enable user to control and define the destination of a vehicle from a base station wirelessly and the advantage comes from the key component, GPS receiver which enable the vehicle to do movement in any direction according to the signal received from the base station without need a track.